Effects of Frying and Storage Conditions On Physicochemical Properties of Palm Olein and Olive Oil Blends - Naghshineh, Mahsa (2009)
The main objective of this study was to investigate the effect of type and concentrations of frying oil namely palm olein (POo) (0, 10, 25, 50, 75, 90 and 100% w/w) and olive oil (OO) (0, 10, 25, 50, 75, 90 and 100% w/w) contents on physicochemical properties of the oil blends. The main physicochemical properties of frying media namely iodine value (IV), peroxide value (PV), anisidine value (AV), totox value (TV), total polar component (TPC), free fatty acid (FFA), cloud point, color and viscosity were assessed as response variables in the present study. The results indicated that the type and concentration of frying media had no significant (p > 0.05) effect on FFA of oil blends; whereas the magnitudes of IV, PV, AV, TV, cloud point, color and viscosity were significantly (p < 0.05) influenced by the type and concentration of frying media. The highest TV (6.10) was shown in the oil blend containing 10% (w/w) POo and 90% (w/w) OO; while the least TV (2.41) was observed in the oil blend containing 90% (w/w) POo and 10% (w/w) OO. This observation could be explained by the high proportion of polyunsaturated fatty acids to monounsaturated fatty acids in former oil blend (POo:OO, 10:90) compared to latter oil blend (POo:OO, 90:10), thus indicating that the increase in the proportion of polyunsaturated/monounsaturated fatty acids led to decrease the chemical stability of the oil blend to the oxidative rancidity. Subsequently, the influence of partial replacement of olive oil (25 and 50% w/w) on frying performance was investigated during 5 consecutive days of frying process. In general, the physiochemical properties of oil blends were significantly (p < 0.05) influenced by the partial replacement of olive oil. The increase in the proportion of polyunsaturated/monounsaturated fatty acid significantly (p < 0.05) decreased the chemical stability of the oil blend during the frying process. The highest changes in AV (79.22), PV (13.55 meq O2/kg) and TV (103.18) were shown by the control (POo, 100% w/w); while the oil blend 2 (POo: OO, 50:50) containing higher concentration of olive oil exhibited the least changes in AV (53.17), PV (2 meq O2/kg) and TV (52.29) during 5 days frying process. Thus, the present study offers that the chemical stability of oil to the oxidative rancidity depends on not only the saturated fatty acid content but also on the proportion of monounsaturated to polyunsaturated fatty acids. The frying time also showed the significant (p < 0.05) effect on TPC of frying media. TPC increased by prolonging the frying time depending on type of frying oil. During 5 days of frying process, the highest increase in TPC (16.51%) was shown by control sample (i.e. POo, 100%); while the frying process using oil blend 2 containing 50% POo and 50% OO resulted in the least increase in TPC (14.63%). Thus, the results showed that the oil blend containing higher olive oil content (i.e. higher oleic acid) provided lower TPC (19.24%) than the TPC (20.92%) of frying media containing higher POo content. The last part of this study was conducted to evaluate the influence of storage time and type of frying media (POo: OO, 100:0, 75:25 and 50:50) as independent variables on the physicochemical properties of oil blends during 60 consecutive days under accelerated condition (60 ºC). The physiochemical properties of oil blends were significantly (p < 0.05) influenced by the independent variables studied. The increase in the proportion of polyunsaturated/monounsaturated fatty acid significantly (p < 0.05) decreased the chemical stability of the oil blend during storage time. The highest changes in AV (38), PV (39.98 meq O2/kg) and TV (117.26) were shown by the control (POO, 100% w/w); while the oil blend 2 (POo: OO, 50:50) containing higher concentration of olive oil (i.e. higher oleic acid content) exhibited the least changes in AV (29.31), PV (26.93 meq O2/kg) and TV (83.38) during 60 days storage. In fact, the oil blend 2 (POo: OO, 50:50) containing higher concentration ratio of oleic acid to linoleic acid (C18:2) was found to be stable during 60 days storage. Thus, the present study suggested that blending palm olein with high monounsaturated fatty acid-contained oil e.g. olive oil can provide the oil blend which is physically more stable than regular POo and remained liquid at ambient temperature.